CURRENT ENVIRONMENTAL CHALLENGES AND THE PROBLEM OF TRANSBOUNDARY WATER USE IN CENTRAL ASIA (Scientific journal of the Fergana State University, 2023)
The article analyzes the issues of transboundary water use in the Aral Sea basin. The authors made an attempt to disclose the parameters of strategic development and the mission of the state bodies of the Republic of Uzbekistan in the rational use of water resources in agriculture and other sectors. The study states that environmental challenges, global warming is the reason for the rapid reduction of glaciers that feed the main water arteries of the region. The relationship between the preservation of peace and stability and the problem of water use in the region is emphasized.